Fluorescent membrane potential assay for drug screening on Kv10.1 channel: identification of BL-1249 as a channel activator - Gómez-Herrera, Mirsha Aseret; Patlán, Enikar; Estrada-Garrido, Armando; Hernández-Cruz, Arturo; Luis, Enoch (Frontiers in Pharmacology, 2023)
Resting membrane potential is a bioelectric property of all cells. Multiple players govern this property, the ion channels being the most important. Ion channel dysfunction can affect cells' resting membrane potential and could be associated with numerous diseases. Therefore, the drug discovery focus on ion channels has increased yearly. In addition to patch-clamp, cell-based fluorescent assays have shown a rapid and reliable method for searching new ion channel modulators. Here, we used a cell-based membrane potential assay to search for new blockers of the Kv10.1, a potassium channel strongly associated with cancer progression and a promising target in anticancer therapy. We found that fluoxetine and miconazole can inhibit the Kv10.1 channel in the micromolar range. In contrast, BL-1249 potentiates Kv10.1 currents in a dose-dependent manner, becoming the first molecule described as an activator of the channel. These results demonstrate that cell-based membrane potential assay can accelerate the discovery of new Kv10.1 modulators.